Transforming Early Childhood Classroom Engagement: An Interactive Cooking Class Approach to Foster Fine Motor and Collaborative Competencies - Sri Wahyuni; Aip Syarifudin; Rina Hizriyani (Qualitative and Quantitative Research Center, 2026)
Passive, worksheet-based instructional routines in early childhood education often restrict sensory-motor exploration and peer interaction, leading to diminished classroom engagement. To address this challenge, this study investigated how an interactive culinary pedagogy transforms behavioral, emotional, and social engagement while fostering fine motor precision and collaborative competencies among preschoolers aged 5–6 years (N = 10). Employing a mixed-methods action research case study design, data were gathered across baseline, Cycle I, and Cycle II observations using validated rubrics evaluated by two independent observers (k ≥ 0.83). Quantitative scores were analyzed using the Wilcoxon signed-rank test and rank-biserial effect sizes, complemented by reflexive thematic analysis of qualitative field notes and video recordings. Results demonstrated statistically significant improvements across all constructs (p < 0.005, r ≥ 0.88). Overall engagement rose from a baseline mean of M = 1.85 (SD = 0.32) to M = 3.70 (SD = 0.21) in Cycle II (Z = -2.82). Fine motor precision advanced from M = 1.60 (SD = 0.28) to M = 3.60 (SD = 0.23) (Z = -2.82), characterized by mature pincer grasps and enhanced hand-eye coordination. Collaborative competencies similarly evolved from parallel play to synchronized group problem-solving (M = 1.45 to M = 3.50, Z = -2.81). As a key theoretical and practical contribution, this study validates an integrated framework of embodied sensory-motor collaboration, establishing culinary pedagogy as a viable dual-targeted intervention that bridges physical manipulation with socio-emotional development in early childhood settings.